Readmission rates are associated with differences in the process of care in acute asthma. Issue 4 (December 1997) - Slack, R; Bucknall, C E
Abstract : OBJECTIVE: To test the hypothesis that sustained differences in readmission rate for acute asthma were associated with variations in clinical practice. DESIGN: Data were collected by retrospective review of case notes, using the criteria recommended by the British Thoracic Society. SETTING: Two city National Health Service (NHS) hospitals that had recorded a sustained difference in readmission rate for acute asthma. SUBJECTS: A random sample of 50 from each hospital, selected from all 16-44 year old patients discharged in 1992 with acute asthma (ninth revision of the international classification of diseases (ICD-9) 493). RESULTS: Hospital A had a lower readmission rate than hospital B. The sample groups were similar for age, sex, deprivation of area of residence, and severity of episode. Systemic corticosteroids were given early more often (p = 0.02) and oral corticosteroids were prescribed at discharge more often (p = 0.04) in hospital A. When a short course of oral corticosteroids was prescribed the duration stated was longer (p = 0.02) and inhaled corticosteroids were started or the dose increased more often (p = 0.02) in hospital A. CONCLUSIONS: These results support the hypothesis that differences in readmission rates for acute asthma are associated with variations in clinical practice. Sustained variation in readmission rates is an outcome of health care, for acute asthma. The findings also support audit of the process of hospital asthma care as a proxy for outcome.